Influence of Leadership Styles on Turnover Intention of employees in the information technology industry: the mediating role of perceived organisational support - Cui, Ke (2022)
Workforce in the information technology (IT) industry has become a critical issue for IT organizations due to high turnover rates. Various leadership styles were recognized as antecedents of turnover intention, and perceived organizational support (POS) also demonstrated a unique role in reducing turnover intention. Thus, it is necessary to explore how these factors interact to assist organizations reduce employee turnover. This research adopts the method of quantitative research and conducts a survey in the form of a questionnaire with a sample of IT industry employees in the United States, the United Kingdom and China. Multiple linear regression analysis was conducted to explore potential correlations between variables. The findings indicate that transformational leadership and transactional leadership has positive impacts on POS and negative impacts on turnover intentions. Narcissistic leadership is negatively correlated with POS and positively correlated with turnover intention. POS as a mediator role to mediate the relationship between transformational leadership, transactional leadership, narcissistic leadership and turnover intentions, respectively.